Exploring EFL Students’ Digital Multimodal Composing (DMC) Affordance: Stories from Vocational School - Dyah Retno Wulan; Nur Arifah Drajati; Slamet Supriyadi (AL-ISHLAH: Jurnal Pendidikan, 2022)
Due to the massive rapid advancement of media and communication technologies, educational institutions all over the world have recently realized the need of encouraging multiliteracies, whether in schools or at universities. There is rising interest in incorporating digital multimodal composition (DMC) into ELT education. While the use of DMC for multiliteracy development is well established, the important question of how DMC could boost English learning, especially in EFL settings, remains unaddressed. This paper analyzes the affordances of DMC for EFL learning using findings from an Indonesian DMC program. Data were collected from interviews and questionnaires which were given to the students. Then the data were analyzed by using interactive model analysis to locate the relevant information with a range of technical, pedagogical, and social affordances, all of which had varying and interconnected effects on their EFL learning. This study revealed that DMC might also allow students to be completely creative with technology in their activities, open up new learning opportunities, and increase students' social awareness. Finally, this study demonstrates how affordances might improve students' involvement with English learning. However, this study is limited only to students from vocational high school. Other researchers are expected to cover a wider area of study and get the experience from teachers who conducted DMC in their classes.